EXPRESSIVE ART THERAPY APPROACH IN REDUCING SELF-HARM AMONG ADOLESCENT - Wan Puteri Nurul Izzah Zakaria; Noorlila Ahmad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Adolescent self-harming behavior is a complex and concerning issue which require a comprehensive and holistic understanding. Expressive art therapy serves as a therapeutic approach to address self-harm among adolescents in which they can express and explore their emotions, thoughts, and experiences in a non-verbal manner by utilizing various art forms. This research aims to explore in-depth self-harming behaviour among adolescents and the implementation of expressive art therapy approach to reduce self-harming behaviour among adolescent. This research employed an action research approach whereby the entire cycle process starting from planning stage to the reflecting stage were completed using one sample as participant engaged in expressive art therapy. Referral volunteered adolescents participated after claiming to involve in self-harm activities. The action research cycle involved nine sessions in a six weeks period. The results found that the adolescents developed self-resilience and could regulate through a suitable personal coping skill thus reducing self-harm behavior. The results also showed that expressive art therapy approach is effective in helping adolescents from relapsing into self-harm behavior. Moreover, the creative process in expressive art therapy approach provided a safe and supportive environment for the adolescents to externalize their distress and develop alternative coping mechanisms.